CARDED AND COMBED YARN EFFECT ON FINISHED FABRIC QUALITY - Mishuk, Aminul Islam; Saha, Tanushree; Sina, Ahmad Saquib; Mostafa, Md. Golam; Sharek, Ahmed Sabab (European Scientific Journal, ESJ, 2015)
Now a day’s most of the buyer of textile industry throughout the world is looking for best quality product. Often buyers are asking to produce finished product from carded or combed yarn. So knowing the performance of product made from cared or combed yarn is getting higher day by day. Yarn is the fundamental unit of fabric. Yarn contains a lot of properties (variables) which can affect dyed fabric finished quality. Carded and combed yarns of same GSM have many different properties because of different manufacturing process. Combed yarn is of superior quality and carded yarn is of inferior quality. The main purpose of this project is to find out or investigate carded and combed yarn effect on dyed fabric finished quality such as Color fastness properties(Rubbing, Wash, Perspiration, K/S value).